Application of Artificial Intelligence to the Politics of Criminal Law - Pajar Pahrudin; Yulindawati Yulindawati; Teresa Dominika Palayukan (Yayasan Adra Karima Hubbi, 2024)
Abstract This study aims to analyze the implications of artificial intelligence (AI) on criminal law and its potential to transform the legal landscape. It explores the challenges and opportunities presented by AI in the context of criminal justice systems. The research adopts a qualitative approach, utilizing a comprehensive literature review to examine the existing legal frameworks and policies related to AI in criminal law. It also analyzes case studies and examples of AI applications in criminal justice to provide a holistic understanding of the subject matter. The findings reveal that AI has the potential to significantly impact various aspects of criminal law, including crime prevention, investigation, evidence analysis, sentencing, and rehabilitation. AI technologies can enhance efficiency, accuracy, and objectivity in decision-making processes. However, they also raise concerns regarding privacy, bias, accountability, and the potential for misuse. The study highlights the need for a robust legal framework that addresses these challenges while harnessing the benefits of AI in criminal law. This study contributes to the growing body of literature on the intersection of AI and criminal law. By examining the implications and potential of AI in the context of criminal justice systems, it provides insights for policymakers, legal professionals, and scholars. The research emphasizes the importance of proactive regulation and ethical considerations to ensure the responsible and fair implementation of AI technologies in criminal law. Keywords: Artificial Intelligence, Politics, Criminal Law